Factors affecting long‐term outcome of transoral surgery for submandibular stones: a follow‐up study of 125 patients. (7th February 2016) - Kim, J.K.; Shin, S.M.; Lee, H.; Lee, S.
Abstract : Objective: To investigate the long‐term results of transoral surgery for submandibular stones and assess factors that may affect the long‐term outcomes. Study design: A follow‐up study including retrospective review of medical records and prospective telephone survey. Setting: Tertiary Hospital. Participants: A total of 125 patients who had undergone transoral surgery for submandibular stones and responded to telephone survey. Main outcome measures: Recurrent obstructive symptoms, tongue paraesthesia. Results: The period between transoral surgery and telephone survey was mean 54.8 months. Eighteen (14.4%) of 125 patients had recurrent obstructive symptoms, and 7 (5.6%) patients showed tongue paraesthesia. Proximal stones ( P = 0.041) and partially removed stones ( P = 0.003) had significant impact on the development of recurrent obstructive symptoms via multivariate analysis. No significant factors for increased risk of tongue paraesthesia were identified. Recurred symptoms could be managed by subsequent transoral surgeries or conservative management. Conclusions: Complete removal of proximal stones and gland‐preserving management of recurred symptoms are the essential elements to achieve good long‐term outcome of transoral surgery for the submandibular stones.